Uso das avaliações externas como suportes pedagógicos na melhoria do ensino de matemática na eef dulcinea gomes diniz - itaiçaba-ce - Silva, Paulo Roberto de Holanda (2019)
This work has as main objective to describe an experiment developed in the E.E.F Dulcinea Gomes Diniz from Itaiçaba-CE which shows the contribution of data's study of the external assessments to improve pedagogical support in the teaching-learning process. It was used a research-action methodology that was divided in 10 steps, among which we can point: diagnostic evaluation; motivation; individualized service; parental involvement and teaching's new technics. The experiment's data allows indicating the necessary redirects in the pedagogic area to accomplish the objectives, which in this case was a high level education for everyone. After two years of the project the results were satisfactory, more than 50% of the students were at the appropriate level and none of them at the very critical level. Based on the results the City's Education Department turned this project into a pedagogic proposal for the entire city's education. Making the due adjustments, every school that didn't accomplish the desired learning level can use this project